Studi Penanganan Konservasi Lahan Di Sub Das Keduang Das Bengawan Solo Kabupaten Wonogiri - Rahman, Mahyaya M.; Harisuseno, Donny; Sisinggih, Dian (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
The presence of reservoir Gajah Mungkur (WGM) has the primary function as flood control, irrigation, drinking water suppliers, and producing electricity. But the great flood of 2008 occurred along the Bengawan Solo River flow due to siltation (sedimentation). Studi JICA ascertainable average annual sediment 1993-2004 period of 3.18 million m3. Sediment Keduang largest river erosion is about 33% of the total sedimentation.The determination of the rate of erosion and sediment in the sub-watershed Keduang with Erosion AVSWAT 2000 obtained a total of 172.2379 tons/ha/year. While the total sediment entering the outlet approximately 1,152,435.58 tons/ha/year. In addition, there are forests only 319.17 ha or 0.87% of total sub-watershed. Vegetatif conservation treatment affects the long-term preservation of nature is a perennial plant that productive and economic value of crop Distance, cocoa, cashew, sugar cane, citrus and grass plants. But mechanical conservation measures only temporary sediment controls such as making buildings or Check Dam.Key words: erosion, sedimentation and conservation